Studies on The Improvement of Students' Pleinair Visual Arts (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
When working outdoors, students face more difficult conditions than in the workshop - wind, cloudiness, the passage of time, changing the color tone of the objective world. Pleinair  painting is also affected by the degree to which shapes vary with distance objects, their illumination depending on the angle of incidence and spectral coloring of light rays. At the same time, tonal and color contrasts caused by the reflection of sunlight from objects and transmission of reflections make up the color richness of the picture. The analysis of educational tasks in plein air painting reveals the need to develop taking into account these professional skills and abilities. In fine arts the psychological structure of each person allows to develop individual approaches to education that help to develop students' artistic thinking and realize their ideas in creative work.